2008
DOI: 10.1007/s10350-008-9248-x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of Sexual Function and Quality of Life After Ileal Pouch-Anal Anastomosis

Abstract: In men, ileal pouch-anal anastomosis does not have an adverse effect on sexual function, whereas sexual function in women seems to improve 12 months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 14 publications
3
64
0
1
Order By: Relevance
“…Samkvaemt niðurstöðum hafði aðgerð ekki marktaek áhrif á kynlíf karlmanna en baetti kynlíf kvenna svo um munaði. 22 Niðurstöður japanskrar rannsóknar bendir hins vegar til þess að aðgerðir sem þessi geti haft töluverð neikvaeð áhrif á kynlíf sjúklinga eftir aðgerð. Nítján af 60 sjúkling-um (31%) lýstu neikvaeðum áhrifum á kynlíf, 24% karlmanna og 38% kvenna.…”
Section: R a N N S ó K Nunclassified
“…Samkvaemt niðurstöðum hafði aðgerð ekki marktaek áhrif á kynlíf karlmanna en baetti kynlíf kvenna svo um munaði. 22 Niðurstöður japanskrar rannsóknar bendir hins vegar til þess að aðgerðir sem þessi geti haft töluverð neikvaeð áhrif á kynlíf sjúklinga eftir aðgerð. Nítján af 60 sjúkling-um (31%) lýstu neikvaeðum áhrifum á kynlíf, 24% karlmanna og 38% kvenna.…”
Section: R a N N S ó K Nunclassified
“…RP-IPAA has been found to be associated with erectile dysfunction and retrograde ejaculation in 2-3% of male patients [60]. Conversely, a considerable rate (22-40%) of dyspareunia or sexual dysfunction has been observed in women with a relevant decline in fertility [60].…”
Section: Surgerymentioning
confidence: 99%
“…Conversely, a considerable rate (22-40%) of dyspareunia or sexual dysfunction has been observed in women with a relevant decline in fertility [60]. Some authors have suggested that intraperitoneal adhesion can be the cause of tubular blockage-related infertility [60]. The laparoscopic approach might reduce the chance of postoperative peritoneal adhesions [61].…”
Section: Surgerymentioning
confidence: 99%
“…26 Both instruments have been used in previous studies on patients with IPAA. 13,14,19,20 Hormonal replacement therapy (HRT) for women and injection or oral therapy for erectile dysfunction for men were also recorded. 27,28 Body image was assessed using a 10-item scale, the Body Image Scale (BIS), consisting of affective items (e.g.…”
Section: Sexual Functionmentioning
confidence: 99%
“…impotence, impaired lubrication, pain during intercourse and desire, vary. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] This aspect of quality of life is poorly considered in standard instruments. Reported improvement of sexual function may be an effect of excision of the source of chronic inflammation and a better general health status.…”
Section: Introductionmentioning
confidence: 99%